Composite nano-particle, pH response type nano-particle and preparation method and application of composite nano-particle and pH response type nano-particle

By using composite nanoparticles and pH-responsive nanoparticles technology loaded with doxorubicin and deferrent in cancer treatment, the side effects of doxorubicin are solved, and efficient targeted delivery and low toxicity of cancer cells are achieved. Enhanced treatment effect.

CN119302927APending Publication Date: 2025-01-14ZHEJIANG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411448347.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing doxorubicin used in cancer treatment has serious side effects, such as cardiotoxicity and myelosuppression, and cannot completely cure cancer. The existing nanoparticles have damage to normal cells and the heart in drug delivery.

Method used

Using composite nanoparticles, doxorubicin and deferrectant are combined in biodegradable poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) technology, and the pH-responsive nanoparticle technology is used to utilize poly The dopamine layer coats core nanoparticles to achieve targeted drug delivery and responsive release in low pH environments.

Benefits of technology

It significantly improves the bioavailability and drug stability of doxorubicin, reduces toxicity and side effects on the heart, enhances the selectivity and therapeutic effect on cancer cells, and protects normal cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119302927A_ABST
    Figure CN119302927A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biological medicine, and particularly relates to a composite nanoparticle, a pH response type nanoparticle and a preparation method and application of the pH response type nanoparticle. The composite nanoparticles provided by the invention comprise poly (3-hydroxybutyrate-co-3-hydroxyvalerate), and adriamycin and an iron removal agent which are loaded in the poly (3-hydroxybutyrate-co-3-hydroxyvalerate). Wherein the biodegradable biopolyester poly (poly (3-hydroxybutyrate-co-3-hydroxyvalerate)) is used as a carrier, so that the bioavailability and the drug stability of the adriamycin can be remarkably improved. The deferrization agent and the anti-cancer drug are combined for use, so that the synergistic treatment effect can be realized, the treatment efficiency is further improved, and normal cells and heart are protected at the same time. Therefore, according to the composite nanoparticle provided by the invention, the doxorubicin and the deferrization agent are jointly entrapped in the biopolyester nanoparticle, two drugs can be delivered at the same time, and the toxicity and side effects of the doxorubicin to the heart are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biomedicine technology, and specifically relates to composite nanoparticles, pH-responsive nanoparticles, and a preparation method and application thereof. Background Art

[0002] Cancer is one of the major diseases threatening human health in the world. At present, humans have made phased progress in the treatment strategy of cancer. The main treatment methods for cancer include surgery, chemotherapy, radiotherapy, immunotherapy and other treatment strategies, but cancer has not been completely cured so far. Therefore, the treatment strategy for cancer still needs further exploration. Nanodrug technology has made significant progress in the field of cancer treatment in recent years. The excellent properties of nanoparticles, such as high surface area, good biocompatibility and controllable drug release properties, make them an important member of the drug delivery system.

[0003] Doxorubicin is a commonly used chemotherapy drug with broad-spectrum anticancer activity, mainly used to treat various cancers such as breast cancer, ovarian cancer and lung cancer. Encapsulation in nanoparticles can effectively improve its therapeutic effect. However, the use of doxorubicin is limited by its severe side effects, such as cardiotoxicity and bone marrow suppression. Summary of the invention

[0004] The purpose of the present invention is to provide a composite nanoparticle, a pH-responsive nanoparticle, and a preparation method and application thereof. The composite nanoparticle provided by the present invention realizes the co-encapsulation of doxorubicin and a ferroxenoic acid agent, has an excellent anti-tumor effect, and reduces damage to normal cells and the heart.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The invention provides a composite nanoparticle comprising poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) and doxorubicin and an iron-removing agent loaded in the poly(3-hydroxybutyric acid-co-3-hydroxyvalerate).

[0007] Preferably, the particle size of the composite nanoparticles is 130 to 300 nm;

[0008] The mass ratio of doxorubicin to poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) is 1:1 to 1:8;

[0009] The iron-deficient agent includes one or more of deferoxamine, deferiprone and 4-[3,5-di(2-hydroxyphenyl)-1,2,4-triazol-1-yl]benzoic acid; the mass ratio of the iron-deficient agent to poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) is 1:1 to 1:6.

[0010] The present invention also provides a method for preparing the composite nanoparticles described in the above technical solution, comprising the following steps:

[0011] dissolving doxorubicin and poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) in an organic solvent to obtain an organic solution;

[0012] The organic solution and the iron removal agent aqueous solution are mixed and emulsified to obtain colostrum;

[0013] The colostrum and the surfactant aqueous solution are mixed and emulsified, and the organic solvent is removed to obtain the composite nanoparticles.

[0014] Preferably, the concentration of doxorubicin in the organic solution is 1 to 40 mg / mL, and the concentration of poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) is 2 to 320 mg / mL;

[0015] The concentration of the iron removing agent in the iron removing agent aqueous solution is 1 to 40 mg / mL;

[0016] The mass percentage of the surfactant in the surfactant aqueous solution is 0.25-5%;

[0017] The volume ratio of the iron removing agent aqueous solution, the organic solution and the surfactant aqueous solution is 1:2:20 to 1:7:60.

[0018] The present invention also provides a pH-responsive nanoparticle, comprising a core nanoparticle and a polydopamine layer coated on the surface of the core nanoparticle; the core nanoparticle is the composite nanoparticle described in the above technical solution or the composite nanoparticle obtained by the preparation method described in the above technical solution.

[0019] Preferably, the particle size of the pH-responsive nanoparticles is 160 to 250 nm; and the thickness of the polydopamine layer is 30 to 50 nm.

[0020] Preferably, the pH-responsive nanoparticles further include functional molecules grafted onto the surface of the polydopamine layer; the mass ratio of the functional molecules to the polydopamine in the polydopamine layer is 1:3 to 3:1;

[0021] The functional molecules include one or more of polypeptides, hyaluronic acid, folic acid and polyethyleneimine.

[0022] The present invention also provides a method for preparing the pH-responsive nanoparticles described in the above technical solution, comprising the following steps:

[0023] The core nanoparticles, dopamine monomers and a first solvent are mixed, and a polymerization reaction is carried out under alkaline conditions to obtain the pH-responsive nanoparticles.

[0024] Preferably, after the polymerization reaction, the pH-responsive nanoparticles, functional molecules and a second solvent are mixed to perform a grafting reaction.

[0025] The present invention also provides the use of the composite nanoparticles described in the above technical solution, the composite nanoparticles obtained by the preparation method described in the above technical solution, the pH-responsive nanoparticles described in the above technical solution, or the pH-responsive nanoparticles obtained by the preparation method described in the above technical solution in the preparation of anti-tumor drugs.

[0026] The present invention provides a composite nanoparticle, comprising poly (3-hydroxybutyric acid-co-3-hydroxyvalerate) and doxorubicin and a ferric chelator loaded in the poly (3-hydroxybutyric acid-co-3-hydroxyvalerate). Among them, the use of biodegradable biopolyester poly (poly (3-hydroxybutyric acid-co-3-hydroxyvalerate)) (PHBV) as a carrier can significantly improve the bioavailability and drug stability of doxorubicin. In addition, PHBV has good biodegradability and biocompatibility and is an ideal material for preparing drug nanoparticles. The ferric chelator is used in combination with anticancer drugs to achieve a synergistic therapeutic effect, further improve the treatment efficiency, and protect normal cells and the heart at the same time. Therefore, the composite nanoparticles provided by the present invention co-encapsulate doxorubicin (DOX) and the ferric chelator in biopolyester nanoparticles, and can deliver the two drugs at the same time, reducing the toxicity and side effects of doxorubicin on the heart. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0028] Figure 1 is a data graph showing the effect of the dosage ratio of doxorubicin to PHBV on the size of PHBV-DOX / DFO nanoparticles as shown in Example 1;

[0029] Figure 2 is a data graph showing the effect of poloxamer 407 content on the size of PHBV-DOX / DFO nanoparticles as shown in Example 2;

[0030] Figure 3 is a data graph showing the effect of high pressure homogenizer processing pressure on the size of PHBV-DOX / DFO nanoparticles shown in Example 3;

[0031] Figure 4 is a data graph showing the effect of the number of high pressure homogenization cycles on the size of PHBV-DOX / DFO nanoparticles as shown in Example 4;

[0032] Figure 5 is a scanning electron micrograph of RGD-PHBV-DOX / DFO-PDANPs obtained in Example 6;

[0033] Figure 6 is the dynamic light scattering graph of RGD-PHBV-DOX / DFO-PDANPs obtained in Example 6;

[0034] Figure 7 This is the in vitro doxorubicin release curve of RGD-PHBV-DOX / DFO-PDANPs obtained in Example 7;

[0035] Figure 8 is the in vitro deferoxamine release curve of RGD-PHBV-DOX / DFO-PDANPs obtained in Example 7;

[0036] Fig. 9 It is a graph showing the inhibition of HepG2 cells by doxorubicin, a physical mixture of doxorubicin and deferoxamine, and the RGD-PHBV-DOX / DFO-PDANPs obtained in Example 7. DETAILED DESCRIPTION

[0037] The invention provides a composite nanoparticle comprising poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) and doxorubicin and an iron-removing agent loaded in the poly(3-hydroxybutyric acid-co-3-hydroxyvalerate).

[0038] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.

[0039] In the present invention, the particle size of the composite nanoparticles is preferably 130-300 nm. In a specific embodiment, the particle size of the composite nanoparticles may be 130 nm, 160 nm, 180 nm or 200 nm.

[0040] In the present invention, the mass ratio of doxorubicin and poly (3-hydroxybutyric acid-co-3-hydroxyvalerate) is preferably 1:1 to 1:8. In a specific embodiment, the mass ratio of doxorubicin and poly (3-hydroxybutyric acid-co-3-hydroxyvalerate) can be 1:1, 1:2, 1:4, 1:6 or 1:8; the iron-deficient agent preferably includes one or more of deferoxamine (DFO), deferiprone (DFP) and 4-[3,5-di (2-hydroxyphenyl) -1,2,4-triazol-1-yl] benzoic acid (DFS). In a specific embodiment, it can be deferoxamine mesylate or deferiprone; the mass ratio of the iron-deficient agent and poly (3-hydroxybutyric acid-co-3-hydroxyvalerate) is preferably 1:1 to 1:6. In a specific embodiment, the mass ratio of the iron-deficient agent and poly (3-hydroxybutyric acid-co-3-hydroxyvalerate) can be 1:1, 1:3 or 1:5.

[0041] In the composite nanoparticles provided by the present invention, the biodegradable biopolyester poly(poly(3-hydroxybutyrate-co-3-hydroxyvalerate))(PHBV) is used as a carrier, which can significantly improve the bioavailability and drug stability of doxorubicin. In addition, PHBV has good biodegradability and biocompatibility and is an ideal material for preparing drug nanoparticles. The iron-removing agent is used in combination with anticancer drugs to achieve a synergistic therapeutic effect, further improve the treatment efficiency, and protect normal cells and the heart at the same time. Therefore, the composite nanoparticles provided by the present invention co-encapsulate doxorubicin (DOX) and the iron-removing agent in the biopolyester nanoparticles, and can deliver the two drugs at the same time, reducing the toxicity and side effects of doxorubicin on the heart.

[0042] The present invention also provides a method for preparing the composite nanoparticles described in the above technical solution, comprising the following steps:

[0043] dissolving doxorubicin and poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) in an organic solvent to obtain an organic solution;

[0044] The organic solution and the iron removal agent aqueous solution are mixed and emulsified to obtain colostrum;

[0045] The colostrum and the surfactant aqueous solution are mixed and emulsified, and the organic solvent is removed to obtain the composite nanoparticles.

[0046] The invention dissolves adriamycin and poly (3-hydroxybutyric acid-co-3-hydroxyvalerate) in an organic solvent to obtain an organic solution. In the present invention, the organic solvent preferably includes one or more of dichloromethane, chloroform and acetone. In a specific embodiment, the organic solvent is preferably dichloromethane or acetone; the concentration of doxorubicin in the organic solution is preferably 1-40 mg / mL. In a specific embodiment, the concentration of doxorubicin in the organic solution may be 2 mg / mL, 10 mg / mL, 20 mg / mL or 40 mg / mL; the concentration of poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) is preferably 2-320 mg / mL. In a specific embodiment, the concentration of poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) may be 10 mg / mL, 20 mg / mL, 30 mg / mL or 40 mg / mL; the mass ratio of doxorubicin to poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) is preferably 1:1-8. In a specific embodiment, the mass ratio of doxorubicin to poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) may be 1:1, 1:2, 1:4, 1:6 or 1:8. The organic solution in the present invention functions as the oil phase (O).

[0047] After obtaining the organic solution, the present invention mixes and emulsifies the organic solution and the iron-removing agent aqueous solution to obtain colostrum. In the present invention, the concentration of the iron-removing agent in the iron-removing agent aqueous solution is preferably 1-40 mg / mL. In a specific embodiment, the concentration of the iron-removing agent in the iron-removing agent aqueous solution can be 2 mg / mL, 10 mg / mL, 20 mg / mL or 40 mg / mL; the mixed emulsification method is preferably: adding the iron-removing agent aqueous solution dropwise to the organic solution and stirring the homogenized solution; the dropping speed is preferably 6-15 mL / min, and in a specific embodiment, the dropping speed can be 6 mL / min, 10 mL / min or 15 mL / min; the rotation speed of the homogenized solution is preferably 6,000-15,000 rpm, and in a specific embodiment, the rotation speed of the homogenized solution can be 6,000 rpm, 8,000 rpm or 12,000 rpm; the time is preferably 5-12 min, and in a specific embodiment, the time of the homogenized solution stirring can be 5 min, 7 min or 12 min. The iron-removing agent aqueous solution in the present invention serves as the inner water phase (W), and the two phases are mixed to obtain colostrum (W / O).

[0048] After obtaining the colostrum, the present invention mixes and emulsifies the colostrum and the surfactant aqueous solution, removes the organic solvent, and obtains the composite nanoparticles. In the present invention, the mass percentage of the surfactant in the surfactant aqueous solution is preferably 0.25-5%. In a specific embodiment, the mass percentage of the surfactant in the surfactant aqueous solution can be 0.25%, 0.5%, 1%, 2.5% or 5%; the surfactant preferably includes polyvinyl alcohol (PVA), bovine serum albumin, human serum albumin or poloxamer, and in a specific embodiment, it can be PVA or poloxamer 407; the volume ratio of the iron-removing agent aqueous solution, the organic solution and the surfactant aqueous solution is preferably 1:2:20-1:7:60, and in a specific embodiment, the volume ratio of the iron-removing agent aqueous solution, the organic solution and the surfactant aqueous solution can be 1:2:20 or 1:4:50; the mixed emulsification method is preferably: adding the colostrum dropwise to the surfactant aqueous solution, and performing homogenization stirring and high-pressure homogenization treatment in sequence; the dripping speed is preferably 6-15 mL / min, and in a specific embodiment, the speed of the dripping is preferably 6-15 mL / min. In the embodiment, the speed of the drop addition can be 6mL / min, 10mL / min or 15mL / min; the speed of the homogenization stirring is preferably 6,000-12,000rpm, and in a specific embodiment, the speed of the homogenization stirring can be 8,000rpm or 10000rpm; the time is preferably 5-9min, and in a specific embodiment, the time of the homogenization stirring can be 5min or 7min; the pressure of the high-pressure homogenization treatment is preferably 50-140MPa, and in a specific embodiment, the pressure of the high-pressure homogenization treatment can be 50MPa, 80MPa, 100MPa, 120MPa or 140MPa; the number of times is preferably 1-10 times, and in a specific embodiment, the number of times of the high-pressure homogenization treatment can be 1 time, 3 times, 5 times, 8 times or 10 times; the removal of the organic solvent is preferably rotary evaporation; the temperature of the rotary evaporation is preferably 40-50°C, and the speed is preferably 40-60rpm. The removal of the organic solvent also preferably includes washing; the washing reagent is preferably water, and the number of washings is preferably 2 times. The surfactant aqueous solution in the present invention serves as an external aqueous phase (W), wherein the surfactant can serve as a stabilizer, and the colostrum is mixed with the external aqueous phase to obtain a multiple emulsion (W / O / W). The high pressure homogenization treatment serves to obtain a stable and uniformly dispersed milky white nanoemulsion. The rotary evaporation serves to remove the organic solvent to obtain a dispersed suspension of composite nanoparticles.

[0049] The preparation method of the composite nanoparticles provided by the present invention uses a double emulsion solvent volatilization method to co-encapsulate a hydrophilic small molecule iron-removing agent and a lipophilic small molecule doxorubicin through PHBV to obtain core nanoparticles, and uses a biocompatible material PHBV to encapsulate the two drugs to obtain spherical nanoparticles. Doxorubicin has a relatively ideal inhibitory effect on tumor cells, but has a strong toxic effect on its heart, while the iron-removing agent can protect the heart and also has an inhibitory effect on tumors. The method adopts a method combining high-speed homogenization and high-pressure homogenization to obtain a nanoparticle core structure, which is simple to operate, the nanoparticle size is controllable, has a more excellent toxicity to cancer cells, and effectively improves biosafety.

[0050] The present invention also provides a pH-responsive nanoparticle, comprising a core nanoparticle and a polydopamine layer coated on the surface of the core nanoparticle; the core nanoparticle is the composite nanoparticle described in the above technical solution or the composite nanoparticle obtained by the preparation method described in the above technical solution.

[0051] In the present invention, the particle size of the pH responsive nanoparticles is preferably 160 to 350 nm. In a specific embodiment, the particle size of the pH responsive nanoparticles may be 170 nm, 200 nm, 250 nm or 300 nm. The thickness of the polydopamine layer is preferably 30 nm to 50 nm. In a specific embodiment, the thickness of the polydopamine layer may be 40 nm or 50 nm.

[0052] In the present invention, the pH-responsive nanoparticles further include functional molecules grafted on the surface of the polydopamine layer; the mass ratio of the functional molecules to the polydopamine in the polydopamine layer is preferably 1:3 to 3:1. In a specific embodiment, the mass ratio of the functional molecules to the polydopamine in the polydopamine layer can be 1:2, 1:1 or 2:1; the functional molecules preferably include one or more of polypeptides, hyaluronic acid, folic acid and polyethyleneimine; the polypeptide has an amino group (-NH 2 ) and / or thiol (-SH), in a specific embodiment, it can be RGD polypeptide. In the present invention, polydopamine contains catechol groups and amine groups, and can undergo grafting reactions with molecules containing thiol groups, imidazole groups, and carboxyl groups. The function of RGD polypeptide is to target cancer cells, and it can bind to the αvβ5 integrin on the surface of cancer cells to drive the nanosystem to target the tumor site. Grafted hyaluronic acid can be used to target hyaluronic acid small molecules of CD44 molecules, which can be grafted with PDA through chemical modification to form a nanocarrier system with specific targeting ability. The amino and carboxyl groups contained in the folic acid molecule can react chemically with the functional groups of PDA. The quinone structure in PDA can react with the amino group in folic acid through Michael addition reaction. Polyethyleneimine can be grafted onto PDA through Michael addition and Schiff base reaction for anti-cancer and other purposes.

[0053] The pH-responsive nanoparticles provided by the present invention are core-core-shell structures, and the core nanoparticles are coated with polydopamine to obtain pH-responsive targeted nanoparticles. The obtained pH-responsive nanoparticles have strong biosafety. The low pH of the tumor microenvironment stimulates the polydopamine shell to crack the doxorubicin and iron-removing agent from the nanoparticles, which can minimize damage to normal cells and the heart, and maximize the selectivity and therapeutic effect of cancer cells. In addition, the nanoparticles obtained by grafting functional molecules on the polydopamine layer also have active targeting to cancer cells.

[0054] The present invention also provides a method for preparing the pH-responsive nanoparticles described in the above technical solution, comprising the following steps:

[0055] The core nanoparticles, dopamine monomers and a first solvent are mixed, and a polymerization reaction is carried out under alkaline conditions to obtain the pH-responsive nanoparticles.

[0056] In the present invention, the dopamine monomer is preferably dopamine hydrochloride and / or dopamine; the first solvent is preferably phosphate buffered saline (PBS) or Tris-HCl buffer; the pH value of the Tris-HCl buffer is preferably 8 to 9.5; the mass ratio of the dopamine monomer to the volume ratio of the first solvent is preferably 0.1 to 2 mg / mL, and in a specific embodiment, the mass ratio of the dopamine monomer to the volume ratio of the first solvent can be 0.5 mg / mL, 1 mg / mL or 2 mg / mL; the temperature of the polymerization reaction is preferably room temperature, and the time is preferably 2 to 5 hours. In the embodiment, the polymerization reaction time can be 2h or 3h; the polymerization reaction is preferably carried out under light-proof and stirring conditions; the stirring speed is preferably 150-200rpm; the polymerization reaction also preferably includes solid-liquid separation; the solid-liquid separation is preferably centrifugal; the speed of the centrifugation is preferably 8,000-15,000rpm, and in a specific embodiment, the speed of the centrifugation can be 12,000rpm or 10,000rpm; the time is preferably 10-20min, and in a specific embodiment, the time of the centrifugation can be 10min or 15min. The mixing in the present invention is to obtain a gray suspension. The dopamine monomer will first be oxidized in an alkaline environment to generate dopamine-quinone. This dopamine-quinone molecule has high activity and can spontaneously react with other dopamine-quinone or unreacted dopamine molecules to undergo Michael addition reaction to form intramolecular cyclization structures. These cyclization structures will further polymerize to form stable polydopamine molecules, forming a layer of polydopamine film on the surface of the nanoparticles to wrap the core nanoparticles.

[0057] In the present invention, after the polymerization reaction, the pH-responsive nanoparticles, functional molecules and a second solvent are mixed to carry out a grafting reaction; the second solvent is preferably a phosphate buffer solution (PBS) or a Tris-HCl buffer solution; the pH value of the Tris-HCl buffer solution is preferably 8-9.5; the mass ratio of the functional molecule to the volume ratio of the first solvent is preferably 0.1-1 mg / mL, and in a specific embodiment, the mass ratio of the functional molecule to the volume ratio of the first solvent can be 0.5 mg / mL, 1 mg / mL or 2 mg / mL; the temperature of the grafting reaction is preferably room temperature, and the time is preferably 0.5-4h, and in a specific embodiment, the time of the polymerization reaction can be 0.5h, 1h or 3h; the grafting reaction is preferably carried out under light-proof and stirring conditions; the stirring speed is preferably 150-200rpm.

[0058] In the present invention, the grafting reaction preferably further comprises solid-liquid separation, washing, resuspension and drying in sequence; the solid-liquid separation is preferably centrifugation; the speed of the centrifugation is preferably 8,000 to 15,000 rpm, and in a specific embodiment, the speed of the centrifugation can be 10,000 rpm or 12000 rpm; the time is preferably 10 to 20 min, and in a specific embodiment, the time of the centrifugation can be 10 min or 15 min; the washing reagent is deionized water, and the number of washings is 3 times; the resuspension reagent is protective agent water Solution; the protective agent in the protective agent aqueous solution includes one or more of mannitol, sucrose and glucose. In a specific embodiment, the protective agent in the protective agent aqueous solution includes mannitol and sucrose; the mass percentage of mannitol in the protective agent aqueous solution is 3-6%, the mass percentage of sucrose is 2-7%, and the mass percentage of glucose is 3-7%; the drying is preferably freeze drying; the freeze drying also includes pre-freezing at -50 to -40°C for 4 to 5 hours; the freeze drying temperature is -75 to -60°C, and the time is 48 to 60 hours.

[0059] The preparation method of the pH-responsive nanoparticles provided by the invention has simple process, is easy to operate and is convenient for production.

[0060] The present invention also provides the use of the composite nanoparticles described in the above technical solution, the composite nanoparticles obtained by the preparation method described in the above technical solution, the pH-responsive nanoparticles described in the above technical solution, or the pH-responsive nanoparticles obtained by the preparation method described in the above technical solution in the preparation of anti-tumor drugs.

[0061] In order to further illustrate the present invention, the composite nanoparticles, pH-responsive nanoparticles, and preparation methods and applications thereof provided by the present invention are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0062] Example 1

[0063] 20 mg of deferoxamine dispersant was dissolved in 1 mL of deionized water by ultrasonic for 10 min to obtain an inner aqueous phase solution (W) with a deferoxamine concentration of 10 mg / mL, and 80 mg of PHBV and doxorubicin (the ratio of doxorubicin to PHBV was 1:1 to 1:8) were dissolved in 4 mL of acetone to obtain an organic solution containing carrier PHBV and drug doxorubicin as the oil phase (O). The aqueous phase solution containing deferoxamine was slowly added to the above organic solution at a dropping speed of 10 mL / min, and processed by a high-speed homogenizer at a speed of 8,000 rpm for 5 min to form colostrum (W / O).

[0064] Poloxamer 407 was dissolved in 50 mL of deionized water as the external aqueous phase, and the concentration of poloxamer 407 was 1.0 wt.%. The prepared colostrum was added to the external aqueous phase solution at a dropping speed of 10 mL / min, and a high-speed homogenizer was used to process for 5 min at a speed of 10,000 rpm to obtain a double emulsion (W / O / W, volume ratio 1:4:50). Subsequently, a high-pressure nano homogenizer was used for further emulsification treatment, and the high-pressure homogenizer processing pressure was 80 MPa, and the number of homogenization cycles was 5 times to obtain a stable and uniformly dispersed milky white nanoemulsion. A rotary evaporator (42 ° C, 40 rpm) was used to remove acetone to obtain a monodisperse suspension of PHBV-DOX / DFO nanoparticles.

[0065] The nanoparticle suspension was washed twice with deionized water and centrifuged to obtain a nanoparticle precipitate, which was then resuspended in a Tris-HCl buffer (10 mM, pH 8.5) containing 2 mg / mL dopamine hydrochloride, stirred at 150 rpm for 3 h, and centrifuged to obtain polydopamine-coated nanoparticles (PHBV-DOX / DFO-PDANPs). After centrifugation at 10,000 rpm for 15 min, the PHBV-DOX / DFO-PDA NPs were resuspended in a Tris buffer (10 mM, pH 8.5) containing 1 mg / mL RGD polypeptide, and stirred at room temperature for 0.5 h to obtain RGD-PHBV-DOX / DFO-PDANPs. The precipitate was collected by centrifugation at 10,000 rpm for 10 min, washed three times, and filtered to obtain the nanoparticle precipitate, which was resuspended in an aqueous solution medium containing mannitol (3%) and sucrose (2%) lyophilization protectants, and freeze-dried at -60°C for 48 h to obtain RGD-grafted nanoparticles (RGD-PHBV-DOX / DFO-PDA NPs) lyophilized powder encapsulating doxorubicin and deferoxamine.

[0066] The effect of the doxorubicin to PHBV ratio w:w of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, and 1:8 on the size of PHBV-DOX / DFO nanoparticles was investigated. The particle size data of PHBV-DOX / DFO nanoparticles under different doxorubicin to PHBV ratios are shown in Figure 1 .

[0067] Depend on Figure 1 It can be seen that the size of PHBV-DOX / DFO nanoparticles first decreases and then increases with the increase of the dosage ratio of doxorubicin to PHBV. When the dosage ratio of doxorubicin to PHBV is 1:1 to 1:8, the nanoparticles are spherical particles with a relatively uniform size distribution. Considering the minimum particle size as the optimal criterion, the dosage ratio of doxorubicin to PHBV is 1:2 to 1:5.

[0068] Example 2

[0069] RGD-PHBV-DOX / DFO-PDANPs were prepared according to the preparation method provided in Example 1, except that the usage ratio of doxorubicin to PHBV was 1:3 w:w, and the effects of the mass percentage of poloxamer 407 in the external aqueous phase on the size of PHBV-DOX / DFO nanoparticles were investigated at 0.25wt.%, 0.5wt.%, 1wt.%, 1.5wt.%, 2.0wt.%, 2.5wt.%, 3wt.%, 3.5wt.%, 4wt.%, 4.5wt.%, and 5wt.%, respectively. The particle size data of PHBV-DOX / DFO nanoparticles under different surfactant concentrations are shown in FIG. Figure 2 .

[0070] Depend on Figure 2 It can be seen that, taking the particle size of PHBV-DOX / DFO nanoparticles as the reference standard, when the mass percentage of poloxamer 407 in the external water phase is 0.25-5wt.%, the size of the nanoparticles shows a trend of gradually decreasing and then increasing, and the nanoparticles are uniformly dispersed and have a small particle size. Considering the minimum particle size as the optimal standard, the content of poloxamer 407 in the external water phase is 0.5-2.5wt.% as the optimal condition.

[0071] Example 3

[0072] RGD-PHBV-DOX / DFO-PDANPs were prepared according to the preparation method provided in Example 1, except that the usage ratio of doxorubicin to PHBV was 1:3 w:w, and the mass percentage of poloxamer 407 in the external aqueous phase was 1.5wt.%. The effects of high-pressure homogenization pressures of 50MPa, 60MPa, 70MPa, 80MPa, 90MPa, 100MPa, 110MPa, 120MPa, 130MPa, and 140MPa on the size of PHBV-DOX / DFO nanoparticles were investigated. The particle size data of PHBV-DOX / DFO nanoparticles under different high-pressure homogenization pressures are shown in FIG. Figure 3 .

[0073] Depend on Figure 3 It can be seen that under the condition of high-pressure homogenization pressure of 50-140MPa, the nanoparticle system is stable and presents uniformly dispersed round particles, and the size of the nanoparticles shows a trend of first decreasing and then increasing. When the homogenization pressure is 80-120MPa, the particle size of PHBV-DOX / DFO nanoparticles is small, so the high-pressure homogenization pressure of 80-120MPa is selected as the best condition.

[0074] Example 4

[0075] RGD-PHBV-DOX / DFO-PDANPs were prepared according to the preparation method provided in Example 1, except that the usage ratio of doxorubicin to PHBV was 1:3, the mass percentage of poloxamer 407 in the external aqueous phase was 1.5wt.%, and the high-pressure homogenization pressure was 90MPa. The effects of high-pressure homogenization times of 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10 on the size of PHBV-DOX / DFO nanoparticles were investigated. The particle size data of PHBV-DOX / DFO nanoparticles under different high-pressure homogenization times are shown in Figure 4 .

[0076] Depend on Figure 4 It can be seen that when the high-pressure homogenization times are 1 to 10 times, the particle size of the nanoparticles shows a trend of first decreasing and then increasing, and the nanoparticles are dispersed more evenly without aggregation. When the homogenization times are 5 to 8 times, the particle size of the PHBV-DOX / DFO nanoparticles is smaller, so the high-pressure homogenization times of 5 to 8 times are selected as the best condition.

[0077] Example 5

[0078] 10 mg of deferoxamine dispersant was dissolved in 1 mL of deionized water by ultrasonic for 10 min to obtain an inner aqueous phase solution (W) with a deferoxamine concentration of 10 mg / mL, 80 mg of PHBV and 20 mg of doxorubicin were dissolved in 4 mL of acetone to obtain an organic solution containing carrier PHBV and drug doxorubicin as the oil phase (O). The aqueous phase solution containing deferoxamine was slowly added to the above organic solution at a dropping speed of 8 mL / min, and processed by a high-speed homogenizer at a speed of 8000 rpm for 5 min to form colostrum (W / O).

[0079] 500 mg of poloxamer 407 was dissolved in 50 mL of deionized water as the external aqueous phase, and the prepared colostrum was added dropwise to the external aqueous phase solution. The prepared colostrum was added dropwise to the external aqueous phase solution at a dropping speed of 8 mL / min, and a high-speed homogenizer was used to treat it at a speed of 10,000 rpm for 5 min to obtain a double emulsion (W / O / W, volume ratio 1:4:50). Subsequently, a high-pressure nano homogenizer was used for further emulsification treatment, the high-pressure homogenizer treatment pressure was 80 MPa, and the number of homogenization cycles was 5 times to obtain a stable and uniformly dispersed milky white nanoemulsion. A rotary evaporator (45°C, 50 rpm) was used to remove acetone to obtain a monodisperse suspension of PHBV-DOX / DFO nanoparticles, and the particle size of the nanoparticles was measured to be 173.25±7.3 nm.

[0080] The nanoparticle suspension was washed twice with deionized water and centrifuged to obtain a nanoparticle precipitate, which was then resuspended in a Tris-HCl buffer (10 mM, pH 8.5) containing 2 mg / mL dopamine hydrochloride, stirred at 160 rpm for 3 h, and centrifuged to obtain polydopamine-coated nanoparticles (PHBV-DOX / DFO-PDANPs). After centrifugation at 10,000 rpm for 15 min, the PHBV-DOX / DFO-PDA NPs were resuspended in a Tris buffer (10 mM, pH 8.5) containing 2 mg / mL RGD polypeptide, and stirred at room temperature for 0.5 h to obtain RGD-PHBV-DOX / DFO-PDANPs. The precipitate was collected by centrifugation at 12,000 rpm for 10 min, washed three times, and filtered to obtain the nanoparticle precipitate, which was resuspended in an aqueous solution medium containing mannitol (3%) and sucrose (2%) lyophilization protectants, and freeze-dried at -60°C for 48 h to obtain RGD-grafted doxorubicin and deferoxamine-loaded nanoparticles (RGD-PHBV-DOX / DFO-PDA NPs) lyophilized powder. The particle size of the nanoparticles was measured to be 220.21±8.2 nm.

[0081] Example 6

[0082] 20 mg of deferoxamine dispersant was dissolved in 1 mL of deionized water by ultrasonic for 10 min to obtain an inner aqueous phase solution (W) with a deferoxamine concentration of 10 mg / mL, 80 mg of PHBV and 26.67 mg of doxorubicin were dissolved in 4 mL of acetone to obtain an organic solution containing carrier PHBV and drug doxorubicin as the oil phase (O). The aqueous phase solution containing deferoxamine was slowly added to the above organic solution at a dropping speed of 12 mL / min, and processed by a high-speed homogenizer at a speed of 8000 rpm for 5 min to form colostrum (W / O).

[0083] 750 mg of poloxamer 407 was dissolved in 50 mL of deionized water as the external aqueous phase, and the prepared colostrum was added dropwise to the external aqueous phase solution. The prepared colostrum was added dropwise to the external aqueous phase solution at a dropping speed of 12 mL / min, and a high-speed homogenizer was used to treat it at a speed of 10,000 rpm for 5 min to obtain a double emulsion (W / O / W, volume ratio 1:4:50). Subsequently, a high-pressure nano homogenizer was used for further emulsification treatment, the high-pressure homogenizer treatment pressure was 70 MPa, and the number of homogenization cycles was 5 times to obtain a stable and uniformly dispersed milky white nanoemulsion. A rotary evaporator (45°C, 60 rpm) was used to remove acetone to obtain a monodisperse suspension of PHBV-DOX / DFO nanoparticles, and the particle size of the nanoparticles was measured to be 161.45±6.3 nm.

[0084] The nanoparticle suspension was washed twice with deionized water and centrifuged to obtain a nanoparticle precipitate, which was then resuspended in a Tris-HCl buffer (10 mM, pH 8.5) containing 2 mg / mL dopamine hydrochloride, stirred at 180 rpm for 3 h, and centrifuged to obtain polydopamine-coated nanoparticles (PHBV-DOX / DFO-PDANPs). After centrifugation at 10,000 rpm for 15 min, the PHBV-DOX / DFO-PDA NPs were resuspended in a Tris buffer (10 mM, pH 8.5) containing 2 mg / mL RGD polypeptide, and stirred at room temperature for 0.5 h to obtain RGD-PHBV-DOX / DFO-PDANPs. The precipitate was collected by centrifugation at 10,000 rpm for 10 min, washed three times, and filtered to obtain the nanoparticle precipitate, which was added to an aqueous solution medium containing mannitol (3%) and sucrose (2%) lyophilization protectants and resuspended. The precipitate was freeze-dried at -60°C for 48 h to obtain RGD-grafted doxorubicin and deferoxamine-loaded nanoparticles (RGD-PHBV-DOX / DFO-PDA NPs) lyophilized powder, and the particle size of the nanoparticles was measured to be 203.55±9.1 nm.

[0085] Example 7

[0086] 20 mg of deferoxamine dispersant was dissolved in 1 mL of deionized water by ultrasonic for 10 min to obtain an inner aqueous phase solution (W) with a deferoxamine concentration of 10 mg / mL, 80 mg of PHBV and 26.67 mg of doxorubicin were dissolved in 4 mL of acetone to obtain an organic solution containing carrier PHBV and drug doxorubicin as the oil phase (O). The aqueous phase solution containing deferoxamine was slowly added to the above organic solution at a dropping speed of 15 mL / min, and processed by a high-speed homogenizer at a speed of 8000 rpm for 5 min to form colostrum (W / O).

[0087] 750 mg of poloxamer 407 was dissolved in 50 mL of deionized water as the external aqueous phase, and the prepared colostrum was added dropwise to the external aqueous phase solution. The prepared colostrum was added dropwise to the external aqueous phase solution at a dropping speed of 15 mL / min, and a high-speed homogenizer was used to treat it at a speed of 10,000 rpm for 5 min to obtain a double emulsion (W / O / W, volume ratio 1:4:50). Subsequently, a high-pressure nano homogenizer was used for further emulsification treatment, the high-pressure homogenizer treatment pressure was 90 MPa, and the number of homogenization cycles was 6 times to obtain a stable and uniformly dispersed milky white nanoemulsion. A rotary evaporator (45°C, 50 rpm) was used to remove acetone to obtain a monodisperse suspension of PHBV-DOX / DFO nanoparticles, and the particle size of the nanoparticles was measured to be 138.24±7.2 nm.

[0088] The nanoparticle suspension was washed twice with deionized water and centrifuged to obtain a nanoparticle precipitate, which was then resuspended in a Tris-HCl buffer (10 mM, pH 8.5) containing 2 mg / mL dopamine hydrochloride, stirred at 160 rpm for 3 h, and centrifuged to obtain polydopamine-coated nanoparticles (PHBV-DOX / DFO-PDANPs). After centrifugation at 10,000 rpm for 15 min, the PHBV-DOX / DFO-PDA NPs were resuspended in a Tris buffer (10 mM, pH 8.5) containing 2 mg / mL RGD polypeptide, and stirred at room temperature for 0.5 h to obtain RGD-PHBV-DOX / DFO-PDANPs. The precipitate was collected by centrifugation at 10,000 rpm for 15 min, washed three times, and filtered to obtain the nanoparticle precipitate, which was resuspended in an aqueous solution medium containing mannitol (3%) and sucrose (2%) lyophilization protectants, and freeze-dried at -60°C for 48 h to obtain RGD-grafted doxorubicin and deferoxamine-loaded nanoparticles (RGD-PHBV-DOX / DFO-PDA NPs) lyophilized powder, and the particle size of the nanoparticles was measured to be 181.62±6.2 nm.

[0089] Example 8

[0090] 40 mg of deferoxamine dispersant was dissolved in 1 mL of deionized water by ultrasonic for 10 min to obtain an inner aqueous phase solution (W) with a deferoxamine concentration of 10 mg / mL, 80 mg of PHBV and 13.33 mg of doxorubicin were dissolved in 4 mL of acetone to obtain an organic solution containing carrier PHBV and drug doxorubicin as the oil phase (O). The aqueous phase solution containing deferoxamine was slowly added to the above organic solution at a dropping speed of 8 mL / min, and processed by a high-speed homogenizer at a speed of 8000 rpm for 5 min to form colostrum (W / O).

[0091] 1250 mg of poloxamer 407 was dissolved in 50 mL of deionized water as the external aqueous phase, and the prepared colostrum was added dropwise to the external aqueous phase solution. The prepared colostrum was added dropwise to the external aqueous phase solution at a dropping speed of 8 mL / min, and a high-speed homogenizer was used to treat it at a speed of 10,000 rpm for 5 min to obtain a double emulsion (W / O / W, volume ratio 1:4:50). Subsequently, a high-pressure nano homogenizer was used for further emulsification treatment, the high-pressure homogenizer treatment pressure was 90 MPa, and the number of homogenization cycles was 7 times to obtain a stable and uniformly dispersed milky white nanoemulsion. A rotary evaporator (48°C, 60 rpm) was used to remove acetone to obtain a monodisperse suspension of PHBV-DOX / DFO nanoparticles, and the particle size of the nanoparticles was measured to be 167.76±5.3 nm.

[0092] The nanoparticle suspension was washed twice with deionized water and centrifuged to obtain a nanoparticle precipitate, which was then resuspended in a Tris-HCl buffer (10 mM, pH 8.5) containing 2 mg / mL dopamine hydrochloride, stirred at 200 rpm for 3 h, and centrifuged to obtain polydopamine-coated nanoparticles (PHBV-DOX / DFO-PDANPs). After centrifugation at 10,000 rpm for 15 min, the PHBV-DOX / DFO-PDA NPs were resuspended in a Tris buffer (10 mM, pH 8.5) containing 1 mg / mL RGD polypeptide, and stirred at room temperature for 0.5 h to obtain RGD-PHBV-DOX / DFO-PDANPs. The precipitate was collected by centrifugation at 10,000 rpm for 12 min, washed three times, and filtered to obtain the nanoparticle precipitate, which was resuspended in an aqueous solution medium containing mannitol (3%) and sucrose (2%) lyophilization protectants, and freeze-dried at -60°C for 48 h to obtain RGD-grafted doxorubicin and deferoxamine-loaded nanoparticles (RGD-PHBV-DOX / DFO-PDA NPs) lyophilized powder, and the particle size of the nanoparticles was measured to be 215.54±7.7 nm.

[0093] Example 9

[0094] 30 mg of deferoxamine dispersant was dissolved in 1 mL of deionized water by ultrasonic for 10 min to obtain an inner aqueous phase solution (W) with a deferoxamine concentration of 10 mg / mL, 80 mg of PHBV and 80 mg of doxorubicin were dissolved in 4 mL of acetone to obtain an organic solution containing carrier PHBV and drug doxorubicin as the oil phase (O). The aqueous phase solution containing deferoxamine was slowly added to the above organic solution at a dropping speed of 14 mL / min, and processed by a high-speed homogenizer at a speed of 8000 rpm for 5 min to form colostrum (W / O).

[0095] 250 mg of poloxamer 407 was dissolved in 50 mL of deionized water as the external aqueous phase, and the prepared colostrum was added dropwise to the external aqueous phase solution. The prepared colostrum was added dropwise to the external aqueous phase solution at a dropping speed of 14 mL / min, and a high-speed homogenizer was used to treat it at a speed of 10,000 rpm for 5 min to obtain a double emulsion (W / O / W, volume ratio 1:4:50). Subsequently, a high-pressure nano homogenizer was used for further emulsification treatment, the high-pressure homogenizer treatment pressure was 100 MPa, and the number of homogenization cycles was 3 times to obtain a stable and uniformly dispersed milky white nanoemulsion. A rotary evaporator (46°C, 60 rpm) was used to remove acetone to obtain a monodisperse suspension of PHBV-DOX / DFO nanoparticles, and the particle size of the nanoparticles was measured to be 188.34±9.2 nm.

[0096] The nanoparticle suspension was washed twice with deionized water and centrifuged to obtain a nanoparticle precipitate, which was then resuspended in a Tris-HCl buffer (10 mM, pH 8.5) containing 2 mg / mL dopamine hydrochloride, stirred at 170 rpm for 3 h, and centrifuged to obtain polydopamine-coated nanoparticles (PHBV-DOX / DFO-PDANPs). After centrifugation at 10,000 rpm for 15 min, the PHBV-DOX / DFO-PDA NPs were resuspended in a Tris buffer (10 mM, pH 8.5) containing 1 mg / mL RGD polypeptide, and stirred at room temperature for 0.5 h to obtain RGD-PHBV-DOX / DFO-PDANPs. The precipitate was collected by centrifugation at 12,000 rpm for 12 min, washed three times, and filtered to obtain the nanoparticle precipitate, which was resuspended in an aqueous solution medium containing mannitol (3%) and sucrose (2%) lyophilization protectants, and freeze-dried at -60°C for 48 h to obtain RGD-grafted doxorubicin and deferoxamine-loaded nanoparticles (RGD-PHBV-DOX / DFO-PDA NPs) lyophilized powder. The particle size of the nanoparticles was measured to be 237.15±9.1 nm.

[0097] Example 10

[0098] 20 mg of deferiprone dispersant was dissolved in 1 mL of deionized water by ultrasonic for 10 min to obtain an inner aqueous phase solution (W) with a deferiprone concentration of 10 mg / mL, 80 mg of PHBV and 26.67 mg of doxorubicin were dissolved in 4 mL of acetone to obtain an organic solution containing carrier PHBV and drug doxorubicin as the oil phase (O). The aqueous phase solution containing deferiprone was slowly added dropwise to the above organic solution at a dropping speed of 10 mL / min, and processed by a high-speed homogenizer at a speed of 8000 rpm for 5 min to form colostrum (W / O).

[0099] 500 mg of poloxamer 407 was dissolved in 50 mL of deionized water as the external aqueous phase, and the prepared colostrum was added dropwise to the external aqueous phase solution. The prepared colostrum was added dropwise to the external aqueous phase solution at a dropping speed of 10 mL / min, and a high-speed homogenizer was used to treat it at a speed of 10,000 rpm for 5 min to obtain a double emulsion (W / O / W, volume ratio 1:4:50). Subsequently, a high-pressure nano homogenizer was used for further emulsification treatment, the high-pressure homogenizer treatment pressure was 90 MPa, and the number of homogenization cycles was 6 times to obtain a stable and uniformly dispersed milky white nanoemulsion. A rotary evaporator (45°C, 50 rpm) was used to remove acetone to obtain a monodisperse suspension of PHBV-DOX / DFP nanoparticles, and the particle size of the nanoparticles was measured to be 149.15±4.2 nm.

[0100] The nanoparticle suspension was washed twice with deionized water and centrifuged to obtain a nanoparticle precipitate, which was then resuspended in a Tris-HCl buffer (10 mM, pH 8.5) containing 2 mg / mL dopamine hydrochloride, stirred at 160 rpm for 3 h, and centrifuged to obtain polydopamine-coated nanoparticles (PHBV-DOX / DFP-PDANPs). After centrifugation at 10,000 rpm for 15 min, the PHBV-DOX / DFP-PDA NPs were resuspended in a Tris buffer (10 mM, pH 8.5) containing 1 mg / mL polyethyleneimine, and stirred at room temperature for 0.5 h to obtain PEI-PHBV-DOX / DFP-PDANPs. The precipitate was collected by centrifugation at 10,000 rpm for 15 min, washed three times, and filtered to obtain the nanoparticle precipitate, which was resuspended in an aqueous solution medium containing mannitol (3%) and sucrose (2%) lyophilization protectants, and freeze-dried at -60°C for 48 h to obtain PEI-grafted doxorubicin and deferiprone-loaded nanoparticles (PEI-PHBV-DOX / DFP-PDA NPs) lyophilized powder, and the particle size of the nanoparticles was measured to be 197.34±4.7 nm.

[0101] Embodiment 11

[0102] 30 mg of DFS dispersant was dissolved in 1 mL of deionized water by ultrasonic for 10 min to obtain an inner aqueous phase solution (W) with a DFS concentration of 10 mg / mL, 80 mg of PHBV and 80 mg of doxorubicin were dissolved in 4 mL of acetone to obtain an organic solution containing carrier PHBV and drug doxorubicin as the oil phase (O). The aqueous phase solution containing DFS was slowly added to the above organic solution at a dropping speed of 15 mL / min, and processed by a high-speed homogenizer at a speed of 8000 rpm for 5 min to form colostrum (W / O).

[0103] 250 mg of poloxamer 407 was dissolved in 50 mL of deionized water as the external aqueous phase, and the prepared colostrum was added dropwise to the external aqueous phase solution. The prepared colostrum was added dropwise to the external aqueous phase solution at a dropping speed of 15 mL / min, and a high-speed homogenizer was used to treat it at a speed of 10,000 rpm for 5 min to obtain a double emulsion (W / O / W, volume ratio 1:4:50). Subsequently, a high-pressure nano homogenizer was used for further emulsification treatment, the high-pressure homogenizer treatment pressure was 80 MPa, and the number of homogenization cycles was 5 times to obtain a stable and uniformly dispersed milky white nanoemulsion. A rotary evaporator (45°C, 60 rpm) was used to remove acetone to obtain a monodisperse suspension of PHBV-DOX / DFS nanoparticles, and the particle size of the nanoparticles was measured to be 163.43±5.2 nm.

[0104] The nanoparticle suspension was washed twice with deionized water and centrifuged to obtain a nanoparticle precipitate, which was then resuspended in a Tris-HCl buffer (10 mM, pH 8.5) containing 2 mg / mL dopamine hydrochloride, stirred at 160 rpm for 3 h, and centrifuged to obtain polydopamine-coated nanoparticles (PHBV-DOX / DFS-PDANPs). After centrifugation at 10,000 rpm for 15 min, the PHBV-DOX / DFS-PDA NPs were resuspended in a Tris buffer (10 mM, pH 8.5) containing 1 mg / mL hyaluronic acid, and stirred at room temperature for 0.5 h to obtain HA-PHBV-DOX / DFS-PDANPs. The precipitate was collected by centrifugation at 10,000 rpm for 15 min, washed three times, and filtered to obtain the nanoparticle precipitate, which was resuspended in an aqueous solution medium containing mannitol (3%) and sucrose (2%) lyophilization protectants, and freeze-dried at -60°C for 48 h to obtain HA-grafted doxorubicin and DFS-loaded nanoparticles (HA-PHBV-DOX / DFS-PDANPs) lyophilized powder. The particle size of the nanoparticles was measured to be 216.64±6.1 nm.

[0105] Example 12

[0106] 40 mg of deferoxamine dispersant was dissolved in 1 mL of deionized water by ultrasonic for 10 min to obtain an inner aqueous phase solution (W) with a deferoxamine concentration of 10 mg / mL, 80 mg of PHBV and 13.33 mg of doxorubicin were dissolved in 4 mL of acetone to obtain an organic solution containing carrier PHBV and drug doxorubicin as the oil phase (O). The aqueous phase solution containing deferoxamine was slowly added to the above organic solution at a dropping speed of 10 mL / min, and processed by a high-speed homogenizer at a speed of 8000 rpm for 5 min to form colostrum (W / O).

[0107] 500 mg of poloxamer 407 was dissolved in 50 mL of deionized water as the external aqueous phase, and the prepared colostrum was added dropwise to the external aqueous phase solution. The prepared colostrum was added dropwise to the external aqueous phase solution at a dropping speed of 10 mL / min, and a high-speed homogenizer was used to treat it at a speed of 10,000 rpm for 5 min to obtain a double emulsion (W / O / W, volume ratio 1:4:50). Subsequently, a high-pressure nano homogenizer was used for further emulsification treatment, the high-pressure homogenizer treatment pressure was 90 MPa, and the number of homogenization cycles was 6 times to obtain a stable and uniformly dispersed milky white nanoemulsion. A rotary evaporator (45°C, 50 rpm) was used to remove acetone to obtain a monodisperse suspension of PHBV-DOX / DFO nanoparticles, and the particle size of the nanoparticles was measured to be 161.25±3.7 nm.

[0108] The nanoparticle suspension was washed twice with deionized water and centrifuged to obtain a nanoparticle precipitate, which was then resuspended in a Tris-HCl buffer (10 mM, pH 8.5) containing 2 mg / mL dopamine hydrochloride, stirred at 180 rpm for 3 h, and centrifuged to obtain polydopamine-coated nanoparticles (PHBV-DOX / DFO-PDANPs). After centrifugation at 10,000 rpm for 15 min, the PHBV-DOX / DFO-PDA NPs were resuspended in a Tris buffer (10 mM, pH 8.5) containing 1 mg / mL folic acid, and stirred at room temperature for 0.5 h to obtain FA-PHBV-DOX / DFO-PDANPs. The precipitate was collected by centrifugation at 10,000 rpm for 15 min, washed three times, and filtered to obtain the nanoparticle precipitate, which was added to an aqueous solution medium containing mannitol (3%) and sucrose (2%) lyophilization protectants and resuspended. The lyophilized powder was freeze-dried at -60°C for 48 h to obtain FA-grafted doxorubicin and deferoxamine-loaded nanoparticles (FA-PHBV-DOX / DFO-PDANPs). The particle size of the nanoparticles was measured to be 204.63±5.3 nm.

[0109] Test Example 1

[0110] The RGD-PHBV-DOX / DFO-PDANPs nanoparticles obtained in Example 6 were subjected to scanning electron microscopy and dynamic light scattering. The obtained scanning electron microscopy and dynamic light scattering images are shown in Figure 5 and Figure 6 .

[0111] Depend on Figure 5 It can be seen that the RGD-PHBV-DOX / DFO-PDANPs nanoparticles appear as single dispersed round spheres detected by scanning electron microscopy, and their particle size is about 200 nm.

[0112] Depend on Figure 6 It can be seen that the results of dynamic light scattering test show that the particle size distribution of RGD-PHBV-DOX / DFO-PDANPs is uniform and single-peaked, the particle distribution is relatively stable, the average nanoparticle size is less than 200nm, the PDI is less than 0.2, and the nanoparticles are negatively charged. Negatively charged nanomedicines improve the enrichment of drugs in tumor sites through the enhanced permeation and retention (EPR) effect.

[0113] Test Example 2

[0114] In vitro drug release evaluation:

[0115] Weigh an appropriate amount of the RGD-PHBV-DOX / DFO-PDANPs freeze-dried powder obtained in Example 7, dissolve the nanoparticles with PBS buffer of different pH values ​​(7.4, 6.5 and 5.0), place the suspension in a dialysis bag (8000-14,000 MWCO), and incubate the entire system at 37°C while stirring at 150 rpm. Extract part of the culture medium at 0.2h, 0.5h, 1h, 2h, 4h, 8h, 12h, 16h, 20h, 24h, 36h, 48h, 72h, 96h, and 120h time points, and add the same volume of fresh PBS and equivalent pH to maintain balance after each extraction of the supernatant. The concentration of the drug in the release medium was determined by HPLC to calculate the cumulative release percentage of the drug and draw an in vitro release curve.

[0116] In vitro release curves of doxorubicin and deferoxamine from RGD-PHBV-DOX / DFO-PDANPs Figure 7 and Figure 8 shown.

[0117] Depend on Figure 7 and Figure 8It can be seen that under the environment of pH 7.4, the release rate of doxorubicin and deferoxamine is slow, and the cumulative release rates after 120 hours are 25.3% and 54.6%, respectively. When the pH is reduced to 5.0, the cumulative release rates of doxorubicin and deferoxamine increase with the decrease of pH, and the cumulative release rates after 120 hours are 79.3% and 85.3%, respectively. This fully demonstrates that RGD-PHBV-DOX / DFO-PDANPs has the characteristics of pH-responsive drug release.

[0118] Test Example 3

[0119] In vitro cytotoxicity study:

[0120] HepG2 cells in logarithmic growth were seeded in 96-well plates at a concentration of 8,000 cells / well and incubated at 37°C and 5% CO. 2 The culture medium was replaced with 200 μL of culture medium containing different concentrations of doxorubicin original drug (1, 5, 25, 50, 75, 100 μg / mL), doxorubicin and deferoxamine physical mixed powder (the mass ratio of doxorubicin and deferoxamine was 1:1) and the RGD-PHBV-DOX / DFO-PDANPs obtained in Example 7, and 6 replicates were performed for each concentration. The culture medium without sample was used as the control group, and the cells were incubated in the dark at 37°C for 48 h. 10 μL of 5 mg / mL MTT solution was added to each culture well and incubated for 4 h. The culture medium was removed, and 150 μL of dimethyl sulfoxide solution was added to each well. The cells were placed in an oscillator for 10 min and the absorbance was detected at 490 nm using a microplate reader.

[0121] Depend on Fig. 9 It can be seen that all sample groups showed concentration-dependent toxic effects on HepG2 cells. The IC50 values ​​of doxorubicin original drug (1, 5, 25, 50, 75, 100 μg / mL), doxorubicin and deferoxamine physical mixed powder, and RGD-PHBV-DOX / DFO-PDANPs group on HepG2 cells were 22.45 μg / mL, 13.23 μg / mL, and 16.13 μg / mL, respectively. At the same doxorubicin concentration, the inhibitory effects of doxorubicin and deferoxamine physical mixed powder group and RGD-PHBV-DOX / DFO-PDANPs preparation group on the growth of HepG2 cells were stronger than that of doxorubicin original drug, because doxorubicin combined with deferoxamine improved the inhibitory effect on HepG2 cells.

[0122] As can be seen from the above examples, the single factor method was used to optimize the formulation composition and preparation process of RGD-PHBV-DOX / DFO-PDANPs. The nanoparticles obtained under the optimized process conditions were small in size, spherical, with high drug loading and encapsulation efficiency, and negatively charged on the surface. In vitro stability and release experiments showed that the nanoparticles had a stable nanostructure under in vitro physiological environment conditions and showed responsive drug release in a low pH environment.

[0123] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A composite nanoparticle, characterized in that: The invention comprises poly (3-hydroxybutyric acid-co-3-hydroxyvalerate) and doxorubicin and iron-removing agent loaded in the poly (3-hydroxybutyric acid-co-3-hydroxyvalerate).

2. The composite nanoparticle according to claim 1, characterized in that The particle size of the composite nanoparticles is 130 to 300 nm; The mass ratio of doxorubicin to poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) is 1:1 to 1:8; The iron-deficient agent includes one or more of deferoxamine, deferiprone and 4-[3,5-di(2-hydroxyphenyl)-1,2,4-triazol-1-yl]benzoic acid; the mass ratio of the iron-deficient agent to poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) is 1:1 to 1:

6.

3. The method for preparing the composite nanoparticles according to claim 1 or 2, characterized in that: The following steps are involved: dissolving doxorubicin and poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) in an organic solvent to obtain an organic solution; The organic solution and the iron removal agent aqueous solution are mixed and emulsified to obtain colostrum; The colostrum and the surfactant aqueous solution are mixed and emulsified, and the organic solvent is removed to obtain the composite nanoparticles.

4. The preparation method according to claim 3, characterized in that: The concentration of doxorubicin in the organic solution is 1 to 40 mg / mL, and the concentration of poly(3-hydroxybutyric acid-co-3-hydroxyvalerate) is 2 to 320 mg / mL; The concentration of the iron removing agent in the iron removing agent aqueous solution is 1 to 40 mg / mL; The mass percentage of the surfactant in the surfactant aqueous solution is 0.25-5%; The volume ratio of the iron removing agent aqueous solution, the organic solution and the surfactant aqueous solution is 1:2:20 to 1:7:

60.

5. A pH-responsive nanoparticle, characterized in that: The invention comprises a core nanoparticle and a polydopamine layer coated on the surface of the core nanoparticle; the core nanoparticle is the composite nanoparticle according to claim 1 or 2 or the composite nanoparticle obtained by the preparation method according to claim 3 or 4.

6. The pH-responsive nanoparticle according to claim 5, characterized in that: The particle size of the pH-responsive nanoparticles is 160-250 nm; the thickness of the polydopamine layer is 30-50 nm.

7. The pH-responsive nanoparticle according to claim 5, characterized in that: The pH-responsive nanoparticles further include functional molecules grafted onto the surface of the polydopamine layer; the mass ratio of the functional molecules to the polydopamine in the polydopamine layer is 1:3 to 3:1; The functional molecules include one or more of polypeptides, hyaluronic acid, folic acid and polyethyleneimine.

8. The method for preparing pH-responsive nanoparticles according to any one of claims 5 to 7, characterized in that: The following steps are involved: The core nanoparticles, dopamine monomers and a first solvent are mixed, and a polymerization reaction is carried out under alkaline conditions to obtain the pH-responsive nanoparticles.

9. The preparation method according to claim 8, characterized in that: After the polymerization reaction, the pH-responsive nanoparticles, functional molecules and a second solvent are mixed to perform a grafting reaction.

10. Use of the composite nanoparticles according to claim 1 or 2, the composite nanoparticles obtained by the preparation method according to claim 3 or 4, the pH-responsive nanoparticles according to any one of claims 5 to 7, or the pH-responsive nanoparticles obtained by the preparation method according to claim 8 or 9 in the preparation of anti-tumor drugs.